Island Archaeology, Model Systems, the Anthropocene, and How the Past Informs the Future. (3rd April 2018) - Fitzpatrick, Scott M.; Erlandson, Jon M.
Abstract: The use of islands as 'model systems' has become particularly relevant for examining a host of important issues in archaeology and other disciplines. As papers in this special issue of the Journal of Island and Coastal Archaeology demonstrate, islands can serve as critical and ideal analytical platforms for observing human populations in the past and their evolutionary histories within complex and insular human ecodynamics. In this paper we address the issue of how islands are also important models for future sustainability and as corollaries for the survival of humans generally. In a sense, island cultures and ecosystems can be seen as microcosms of the issues we have faced as humans, and provide important insights for understanding the fate of our species, particularly as it pertains to the exploration and colonization of new worlds.